Effect of Lactobacillus reuteri on intestinal microbiota and immune parameters: Involvement of sex differences. (February 2019) - He, Jiayi; Wang, Wenwen; Wu, Zhen; Pan, Daodong; Guo, Yuxing; Cai, Zhendong; Lian, Liwei
Graphical abstract: The aim of this research is to investigate the possible probiotic role of Lactobacillus reuteri DMSZ 8533 in immunomodulation and effect on fecal microbiota composition using a BALB/c model. Our results demonstrated that L. reuteri exerted a positive effect on the immune response in females groups and the greatest difference in microflora between the sexes. Highlights: L. reuteri DMSZ 8533 demonstrates stronger survival rate under stimulated gastrointestinal conditions. L. reuteri DMSZ 8533 possesses potential immunostimulatory properties. L. reuteri DMSZ 8533 involves sex differences both in microbial correlation and immunomodulation. Abstract: Probiotic candidate Lactobacillus reuteri DMSZ 8533 was screened out in vitro based on a relatively higher gastrointestinal tolerance and moderate adhesiveness. The organ index (spleen, thymus and liver), Interleukin-12 (IL-12), tumor necrosis factor-α (TNF-α), T-lymphocytes (CD3-, CD4- and CD-8 positive cells) and fecal microbiota composition were also investigated in BALB/c mice. Results showed a significant higher level of IL-12 at low-dose L. reuteri treated group in both females and males. The relative abundance of phylotypes in the phylum Bacteroidetes and Firmicutes exhibited a reserve shift between sexes after L. reuteri intervention. Meanwhile, the relative abundance of several taxa also differed markedly between sexes at low-dose group, together with microbiota diversity. Our finding demonstrates the importance of L. reuteri DMSZ 8533 as a potential probiotic strain with an immunomodulatory effect, which could also alter the microbiota composition depending on the sex of the host.